RI 6820 Determination Of Cesium And Rubidium By Flame Photometry - Kenneth R. Farley (The National Institute for Occupational Safety and Health (NIOSH), 1966)
The Bureau of Mines developed a rapid and accurate flame photometric procedure for determining cesium and rubidium in ores and in products associated with the extractive metallurgy of these elements. The effect of associated ions is neutralized by addition of buffer solution; alkali metal effects are neutralized by parallel analyses made on standard solutions similar in composition to the sample being studied. The overall accuracy of the method is within 2.5 pct of the amount of cesium or rubidium present; the range from 1 to 25 pct is the most accurate.